Profil Pekerja Rumah Tangga (PRT) Di Indonesia Dan Strategi Perlindungannya - Ari Yuliastuti (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2017)
Domestic Workers (PRT) is the most difficult object of labor inspection and protection.. The working pattern of domestic workers who are always behind the door makes supervision of how it works is difficult to detect. Until now, there is no fixed data on PRT profile in the world in general and Indonesia in particular. This study tries to see the profile of domestic workers using National Labor Force Survey data (Sakernas) conducted by BPS in2012 until 2015. PRT Data profiles and discussion can be concluded that domestic workers dominated by women, married status, elementary school equivalent, located in the region urban areas and with low wages of less than Rp. 500,000. One thing that should be underlined is the presence of domestic workers under age. This is certainly very ironic considering that it is not the time for children to be in the working world to becomedomestic workers. The profile of the Indonesian PRT in such a way will determine how appropriate the pattern of protection is. The ILO gives several countries that are categorized as successful in drafting the rules on the protection of domestic workers, namely in South Africa and the Philippines. Indonesia can adopt some rules from both countries by adjusting the facts in the profile of domestic workers according to Sakernas data.